L’introduction de la notion de service environnemental et écosystémique à Madagascar - Fano Andriamahefazafy; Cécile Bidaud; Philippe Méral; Georges Serpantié; Aurélie Toillier (VertigO)
This article aims to identify the modalities of the introduction and adoption of the ecosystem/environmental services (ES) notion at Madagascar, a biodiversity hot spot with low human development. The research privileged documentary study and interviews. The analysis confirms the importance of the international donors and NGO, promoting it so much at the macro-institutional level, that at the local action level. Several steps are identified through a historical analysis: (1) End of the 90s: exploratory research on the total value of the forest products (academic research, forest administration, donors). (2) 2000-2004: advanced research with studies of economists dedicated to the sustainable financing and to the extension of the network of protected areas. (3) From 2004: implementation of PSE, by order of importance: carbon sequestration, hydrological services, preservation of the biodiversity. The actors try to lobby for a project of national policy, what marks one difference with the Costa Rica process, where SE and PSE were introduced by a forest law in 1996. The preservationist circle has adopted this notion but it is not accepted by all the development actors yet. Furthermore there are multiple manners in Madagascar to express and to interpret the notion. As educational notion promoting the environmental consciousness or as new justification of policy plans, the notion testifies also of a transformation of vision of the preservation. Its development is not exempt from opportunism for the financing of the intermediate institutions in several sectors (forest, agriculture, energy).